Once Good, Always Good? Testing Nudge's Spillovers on Pro Environmental Behavior. Issue 3 (April 2022) - Clot, Sophie; Della Giusta, Marina; Jewell, Sarah
It is a common assumption to believe that encouraging pro environmental behavior (PEB) in one domain would lead to increased PEB in other domains (best-case scenario) or just be restricted to the initial targeted domain (worst-case scenario). Evidence from a rapidly growing literature on moral licensing suggests that interventions targeting behavioral change could lead to an even worse scenario, with individuals starting to underperform in one domain, as a compensation for their good performance in other domains. We propose to study the dynamic of PEBs when individuals are exposed to a specific nudge (priming) via an original experiment designed to capture actual behavior. We found that priming could increase PEB, but does not thwart moral licensing. Primed individuals end up doing worse than non-primed individual under a moral licensing condition. A more comprehensive view of the mechanisms underlying behavioral change is essential to support sustainable policies.